STRATEGI PREVENTIF PELECEHAN SEKSUAL DI PESANTREN DI INDONESIA: PERSPEKTIF SOSIOLOGI AGAMA - Abdul Majid (CV The Journal Publishing, 2023)
ABSTRACT: Islamic boarding schools have been an integral part of the culture and history of Indonesian society, and they play an important role in preserving and spreading Islamic religious values. However, in several regions in Indonesia today there are various cases of sexual violence or sexual harassment and more surprisingly these cases appear and are found in Islamic school institutions, namely pesantren. This study aims to analyze the preventive strategy of sexual harassment in pesantren in Indonesia: a sociology of religion perspective and focuses on the prevention of sexual harassment in pesantren and its obstacles. Using a descriptive qualitative method. Data sources were obtained from databoks/databases, BPS, literature reviews, official websites, and regulations. The data analysis technique uses the Nvivo 12 Plus analysis technique through the crosstab feature. The results showed that the preventive strategy of sexual harassment in pesantren in Indonesia: a sociology of religion perspective through indicators of supervision, socialization, education, rules, and facilities. That the preventive strategy in sexual violence from the perspective of religious sociology is that pesantren must provide counseling and protection services to pesantren students, socialize related to the prevention of sexual violence through education in pesantren and Islamic studies, apply fair laws for perpetrators of sexual violence which aim to provide justice for victims of sexual violence, hold parenting for parents of students regularly. Education and awareness about the dangers of sexual violence, as well as support and protection for victims of sexual violence, are essential to prevent and address this issue. Sexual violence is a crime that cannot be justified under any circumstances. Various measures, including education, advocacy, victim support, and effective law enforcement, are needed to prevent and address sexual violence. Keywords: sexual harassment, pesantren, sociology of religion.